A non-invasive method for the assessment of gingival thickness in the aesthetic zone and the concept of the gingival geometric ratio in an Asian population. Issue 3 (March 2023) - Chow, R.L.K.; Lau, S.L.; Leung, Y.Y.; Chow, J.K.F.
Abstract: The aim of this study was to investigate the gingival thickness and biologic width in the aesthetic zone (maxillary central and lateral incisors) in an Asian population using cone beam computed tomography (CBCT) as a non-invasive measurement method, prior to immediate implant placement. The gingival geometric ratio is introduced as a new parameter for assessing soft tissue stability and hence predicting the aesthetic outcome. The gingival thickness, biologic width category (normal, high, and low crest), and gingival geometric ratio (shape and configuration of the gingival tissues) were assessed for 171 central and 175 lateral incisors on high-resolution CBCT images. Thick gingivae were found in 93.6% of the central incisors and 64% of the lateral incisors ( P  < 0.001). The difference in thickness between the central and lateral incisors was statistically significant ( P  < 0.001). Regarding the biologic width of the facial gingival tissue, the majority of central (64.8%) and lateral (64.3%) incisors were categorized as low crest (>3 mm). The study found that most of the gingivae of the maxillary central incisors were thick, while thin gingivae were more prevalent in the lateral incisors. Therefore, an individual patient may have different gingival thickness types, and 'one individual, one gingival biotype' may not be true. Furthermore, the majority of the facial gingival tissues of the maxillary incisors were found to be low crest.